Kaçarlar Döneminde (1779-1925) Minyatür Portreli Nişanlar - Uzun, Tolga (Journal of History Culture and Art Research, 2019)
Portrait Miniatures in Qajar Era (1779-1925) Abstract It has been known that hanging up the miniature portraits of the rulers on the neck or attaching them to the collar has been an expression of obedience to the ruler for the aristocrats or court members. In 16th Century, this tradition was popular at English and French courts. Later it expanded and was used for different purposes. At the beginning of the 19th Century, rulers of Eastern Muslim states such as Qajars in Iran and the Ottomans adopted this western tradition, and they delivered these miniature portraits as an order for state officials and upper classes personalities. In this article, we have dealt with portraited orders of Qajar rulers of Iran in 19th century. They have been evaluated according to subject, style and iconography. Finally, we have discussed their relations with surrounding cultures. In the first part of the study, early examples of the Tudor dynasty in England are presented. Afterwards, examples of Feth Ali Shah, Muhammed Shah and Nasreddin Shah periods were examined and the distinguishing features of these portraits were analyzed. Öz Avrupa saraylarında hükümdarların minyatür portrelerinin saraylılar ve soylular tarafından yakaya ya da boyuna asılması hükümdara bağlılığın bir ifadesi olarak bilinmektedir. 16. Yüzyılda İngiliz ve Fransız saraylarında popüler olan bu âdet, zaman içerisinde yaygınlaşmış ve farklı amaçlarla kullanılmıştır. 19. yüzyılın başından itibaren İran ve Osmanlı gibi Müslüman doğulu ülkelerin hükümdarları, batılı bu âdeti benimseyerek, üst düzey memurlara ve devlet yetkililerine bir nişan olarak dağıtmıştır. Bu çalışmada 19. yüzyılda İran’da Kaçar hükümdarlarının portreli nişanları ele alınmış, konu üslup ve ikonografik açıdan değerlendirilip, çevre kültürler ile bağlantıları tartışılmıştır. Çalışmanın ilk bölümünde Minyatür portrelerle ilgili İngiltere’de Tudor hanedanlığı dönemine ait erken örneklere yer verilmiştir. Daha sonra Kaçarlar döneminde Feth Ali Şah, Muhammed Şah ve Nasreddin Şah dönemleri ile ilgili örnekler incelenmiş ve bu portrelerin ayırt edici özelliklerinin neler olduğu analiz edilmiştir.